Analisis Kecenderungan Mengkonsumsi dan Menabung Rumah Tangga Buruh Pelabuhan (TKBM) Kota Gorontalo - Indriyani Mandagi; Fachrudin Zain Olilingo; Sri Endang Saleh (Masyarakat Ekonomi Syariah Bogor, 2024)
The income of workers in North Leato Village, Dumbo Raya District, reaches Rp. 3,600,000 per month. The study shows that there is a very significant relationship between the income and household consumption level of port workers of loading and unloading workers (TKBM), with an F value of 126,680 and a significance level of 0.000. This confirms that income plays an important role in determining consumption patterns, where the increase in income increases spending on daily needs. The Marginal Propensity to Consume (MPC) value of 3 and the Marginal Propensity to Save (MPS) value of 1 indicate people's tendency to spend more than save, reflecting the priority of meeting basic needs in low-income groups.